2011
DOI: 10.1373/clinchem.2010.156893
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of CYP21A1P in a German Population to Aid in the Molecular Biological Diagnosis of Congenital Adrenal Hyperplasia

Abstract: BACKGROUND The high homology between the CYP21A2 (cytochrome P450, family 21, subfamily A, polypeptide 2) and CYP21A1P (cytochrome P450, family 21, subfamily A, polypeptide 1 pseudogene) genes is the major obstacle to risk-free genetic diagnosis of congenital adrenal hyperplasia, especially regarding the quantification of gene dosage. Because of the lack of a comprehensive study providing useful information about the detailed genetic structure of CYP21A1P, we used a large data set to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Therefore, identification of CYP21A2-like genes and duplicated CYP21A2 genes using either a two-step CYP21A2 amplification (Kharrat et al 2011;Kleinle et al, 2009;Koppens et al 2000;Parajes et al 2008;Wedell et al 1994) or an allele-specific PCR amplification of the CYP21A2 gene (Cantürk et al 2011) may produce PCR drop-off, because it might not be able to distinguish whether CYP21A2 exists downstream of the XB or XA gene. Predictably, the MLPA assay might simultaneously "catch" both the CYP21A2-like (or duplicated CYP21A2) downstream of the TNXA and the CYP21A2 genes downstream of the TNXB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, identification of CYP21A2-like genes and duplicated CYP21A2 genes using either a two-step CYP21A2 amplification (Kharrat et al 2011;Kleinle et al, 2009;Koppens et al 2000;Parajes et al 2008;Wedell et al 1994) or an allele-specific PCR amplification of the CYP21A2 gene (Cantürk et al 2011) may produce PCR drop-off, because it might not be able to distinguish whether CYP21A2 exists downstream of the XB or XA gene. Predictably, the MLPA assay might simultaneously "catch" both the CYP21A2-like (or duplicated CYP21A2) downstream of the TNXA and the CYP21A2 genes downstream of the TNXB.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR described by Cantürk et al used 2 primers in the 5′ flanking sequence specific for CYP21A2 and CYP21A1P genes, whereas the other 2 primers that are positioned in the 3′ end were specific for 2 genes. Although this PCR is indeed suitable for detecting CYP21A2, CYP21A1P, and the copy number of these two genes, it did find out variants via transfer from the CYP21A2 to CYP21A1P gene (Cantürk et al 2011), which is the CYP21A2-like gene with the 5′end of the CYP21A2 sequence and 3′ end of the CYP21A1P sequence (Tsai et al 2011). Cantürk et al (2011) successfully characterized 200 German populations by this method and found there were 40 potentially variable positions in CYP21A2 which were conserved in CYP21A1P, and 14 CYP21A1P variants were detected.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations